Using reverse genetics in screening for host resistance of arabidopsis plants to small cabbage white butterfly pieris rapae herbivory. - Okayo, Robert; Andika, Darius Otiato (International Journal of Scientific Engineering and Applied Science, 2015)
Small cabbage white butterfly Pierisrapaeis one of the most destructive specialist herbivores of the Brassicaceae plants. Chemical application has been used for a long time to control P. rapae but this has been shown to have major draw backs. Owing to their disadvantages, we investigate in this study, the host plant resistance as an alternative control measure for specialist insect P. rapae. T-DNA mutant Arabidopsis plants were screened for their variation in response to P. rapae. None choice and two-choice test were conducted on 30 and 2mutants respectively. For the none choice test, four mutants showed a difference response in comparison to the wild type as measured by biomass reduction. These mutants were disrupted in AT1G09920 (TRAF-TYPEZINC FINGER-RELATED), AT1G79460 (ENT-KAURENE SYNTHASE 1), AT1G10070 (BRANCHED-CHAIN AMINO ACIDTRANSFERASE 2) and AT1G10090 (EARLY-RESPONSIVE TO DEHYDRATION 4). For the two-choice test, one mutant showed a difference response in comparison to the wild type as measured by larvae preference. This was disrupted in AT2G24210 (TERPENE SYNTHASE 10). This study concludes by recommending validation experiment and research to uncover 582 the molecular basis of these finding sand then transfer these novel genes to crop plants.
Keywords: Arabidopsis thaliana; Pieri srapae; Host plant resistance; Mutant; Genes